Thermal Seasons Definition in Iraq - al-Jubouri, Hana; Al-Sabhany, Khamis (Al-Adab Journal, 2024)
One of the most important and difficult aspects of climatology studies is defining seasons. In this study, thermal seasons are defined based on the daily average temperature for a period of 65 years (1956-2021), after determining a relative temperature threshold for the beginning and end of each season. The average temperature from 1956 to 2021 was used to determine; the start and end of summer, when the temperature exceeded up and below the 75th percentile, respectively. The 25th percentile was established as the temperature threshold for winter, and what is between them were considered to be a transitional seasons. The results showed that the characteristics of the four seasons differ from the traditionally defined seasons. The summer season is the longest in southern, central and western Iraq, while the winter season is the longest in northern Iraq. This is due to the factors of altitude, and distance from sources of warm and cold air masses. The results also showed that the transitional seasons (autumn and spring) are short and have less spatial variation than the main seasons (summer and winter). The results also suggested that the summer season started relatively earlier in central and southern Iraq compared to northern Iraq and ends later, while winter begins relatively later in the center and south and ends earlier, compared to stations in northern Iraq.